A new Centaurea L. (Asteraceae) species from Turkey. (3rd September 2017) - Uysal, T.; Hamzaoğlu, E.
Abstract: A new Centaurea L. (Asteraceae) species from Turkey is described and illustrated. Centaurea mersinensis Uysal and Hamzaoğlu exists on calcareous slopes in Pinus brutia forests of Aydıncık (Mersin) in southern Anatolia. It belongs to C . sect. Phalolepis (Cass.) DC., and taxonomically its closest relative is C. lycaonica . Diagnostic morphological characters from very similar taxa are provided, and a key is provided that includes related species of sect. Phalolepis from Turkey. The geographical distribution of the new species and relatives of the same section are mapped. The chromosome number of C. mersinensis, 2 n = 18, counted in root tips, is also reported and illustrated.